Exploration of Student’s Mathematical Connection Ability in PjBL with Ethnomathematics Nuance (Department of Mathematics, Universitas Negeri Semarang, 2022)
The Merdeka Curriculum is one of the government's efforts to recover education after being affected by the Covid-19 pandemic, through project-based learning and Pancasila student profiles. The purpose of this study was to explore students' mathematical connection skills through project based learning (PjBL) with ethnomathematics in the form of painting the motifs of batik or tenun on cartesian diagrams as the implementation of the Merdeka Curriculum. This research was qualitative research with data triangulation. The research data will be obtained through interviews, observations, and project activities carried out by 15 students of class XI IPA 2 at SMAN 11 South Tangerang City. The results showed that the use of weaving motifs in project-based learning can facilitate students' mathematical connection skills, create meaningful and contextual learning as an embodiment of the Merdeka Curriculum to restore teaching and learning activities due to the impact of COVID-19.